Motivation to use Online Learning Communities: A methodological outline - Niven, Jennifer; Harris, Rachel A.; Williams, Dorothy (Proceedings of the International Conference on Networked Learning, 2002)
This paper details the importance of motivation in driving and developing an online community. Methodological approaches in this area are still in development hence this paper outlines the use of retrospective discourse analysis, and the need for stimulated recall to test the motivational factors used and experienced by both tutors and students for an online learning course at The Robert Gordon University. It outlines the use of a section of Keller’s ARCS (Attention, Relevance, Confidence, Satisfaction) model in developing a coding scheme and stable background to the research, allowing relatively unbiased testing of the various hypotheses in studying e-learning. Results will ultimately be illustrated through the creation of a motivational framework to aid in the creation of future e-learning communities.